Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/00273171.2016.1243461
|View full text |Cite
|
Sign up to set email alerts
|

Is the Bifactor Model a Better Model or Is It Just Better at Modeling Implausible Responses? Application of Iteratively Reweighted Least Squares to the Rosenberg Self-Esteem Scale

Abstract: Although the structure of the Rosenberg Self-Esteem Scale (RSES; Rosenberg, 1965) has been exhaustively evaluated, questions regarding dimensionality and direction of wording effects continue to be debated. To shed new light on these issues, we ask: (1) for what percentage of individuals is a unidimensional model adequate, (2) what additional percentage of individuals can be modeled with multidimensional specifications, and (3) what percentage of individuals respond so inconsistently that they cannot be well m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
195
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(214 citation statements)
references
References 48 publications
(63 reference statements)
9
195
1
2
Order By: Relevance
“…The bifactor model's flexibility can also enable it to show superior global fit than alternatives, even when the other models were themselves used to simulate data (33,(38)(39)(40)(41)(42)(43)(44)(45)(46). For example, skewed item distributions and unmodeled cross-loadings or correlated residuals can all lead fit statistics to favor the bifactor model over a correlated-factors model (with no general factor), even if the correlatedfactors model more accurately describes the true structure (46,47).…”
Section: Biological Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…The bifactor model's flexibility can also enable it to show superior global fit than alternatives, even when the other models were themselves used to simulate data (33,(38)(39)(40)(41)(42)(43)(44)(45)(46). For example, skewed item distributions and unmodeled cross-loadings or correlated residuals can all lead fit statistics to favor the bifactor model over a correlated-factors model (with no general factor), even if the correlatedfactors model more accurately describes the true structure (46,47).…”
Section: Biological Psychiatrymentioning
confidence: 99%
“…For example, skewed item distributions and unmodeled cross-loadings or correlated residuals can all lead fit statistics to favor the bifactor model over a correlated-factors model (with no general factor), even if the correlatedfactors model more accurately describes the true structure (46,47). The bifactor model's flexibility can also result in good model-data fit even when used with very noisy data or nonsense response patterns (33,45). Thus, it is inappropriate to use global fit statistics to evaluate the bifactor model or favor it over alternative models (29,48).…”
Section: Biological Psychiatrymentioning
confidence: 99%
“…This model evaluates how well a general factor, in addition to specific factors, account for the latent structure of a measure. 22 For this model, we included three specific factors matching those from the three-correlated-factors model, each with the same items loading on the Burdens of Kidney Disease, Symptoms and Problems of Kidney Disease, and Effects of Kidney Disease factors as described above, except the factors are left uncorrelated. In addition, each item loads directly onto a general factor (Supplemental Appendix 2 [Supplemental Figure 4]).…”
Section: Examination Of a Kdqol-36 Compositementioning
confidence: 99%
“…Some studies do find that the general factor in a bifactor model is defined by distress (Lahey et al, 2012;Lahey et al, 2015;Olino et al, 2014;Waldman et al, 2016), but others find that the general factor is defined by externalizing (Castellanos-Ryan et al, 2016), thought disorder (Caspi et al, 2014), or even autism spectrum disorders (Martel, Pan, et al, 2017;Noordhof et al, 2015). These cross-study discrepancies have given rise to a dizzying array of interpretations of the p-factor , but are also potentially consistent with the bifactor model's tendency to fit any data (Reise et al, 2016).…”
Section: Summary and Implicationsmentioning
confidence: 97%
“…First, bifactor models are vulnerable to overfitting data, engendering their parameter estimates unstable (e.g., Bonifay, 2015;Reise, Kim, Mansolf, & Widaman, 2016). Second, various simulation studies have demonstrated that bifactor models are prone to fitting any possible data, including potentially invalid (Reise et al, 2016) or random response patterns (Bonifay & Cai, 2017). Third, numerous simulation studies have demonstrated that bifactor models invariably show preferential fit compared with higher-order and correlated factors models even when the population ("true") model does not follow a bifactor structure (Greene et al, in press;Maydeu-Olivares & Coffman, 2006;Morgan et al, 2015;Murray & Johnson, 2013).…”
Section: Bifactor Models and Their Applications To Psychopathologymentioning
confidence: 99%